Ultrasonic parameter measurement as a means of assessing the quality of biodiesel production. (1st April 2019) - Baêsso, Raphaela M.; Costa-Felix, Rodrigo P.B.; Miloro, Piero; Zeqiri, Bajram
Graphical abstract: Highlights: Ultrasound multifrequency system can measure SoS and Att of pure oils and biofuels blends. Equivalence for SoS and Att in vegetable oils with similar composition was disclosed. Low concentration of contamination that can be assed with ultrasound technique. The method accuracy and robustness were metrologically assessed. Abstract: Whilst fossil fuels have been an industrial driver for many decades, environmental concerns related to global warming have driven the development of alternative energy sources, such as the generation of biodiesel from vegetable oils. For a biodiesel to be commercialised, it must meets property and quality requirements from International Standards. Most of these checks must be performed off-line, with significant costs in terms of shutdown time and testing. On the other hand, ultrasound measurement can provide an in-line monitoring tool to assess the advance of transesterification. Although this was highlighted in previous works, hitherto this has not been the subject of a detailed metrological approach to define the uncertainty associated with ultrasound techniques applied to biodiesel and related liquids. This paper presents such research and addresses measurement of two ultrasound parameters, Speed of Sound (SoS) and attenuation coefficient (Att), and their capability of assessing macroscopic characteristics of the biodiesel. The liquids tested were pure edible oils (vegetable, corn, and sunflower), castor oil, pure biodiesel (B100), as well as blends of biodiesel with common contaminants or by-products related to biodiesel transesterification. Details of the biodiesel manufactured were varied, using different stirring speeds of rotation (200 rpm and 550 rpm), temperatures (40 °C and 50 °C), and KOH catalyst concentrations (0.2% and 1.5%). Contaminants added to pure biodiesel were methanol (0.10% and 0.20%), glycerol (0.10% and 0.15%) and triglyceride (2%). The acoustic characteristics of these liquids were determined relative to water using a broadband through-transmission substitution method covering the frequency range 1–20 MHz. Normalized error analysis has been applied to assess the equivalence of experimental results, as well as to discriminate the detection sensitivity of the technique. From the measurements, all edible oils showed equivalent experimental values for SoS and Att over the usable frequency band 2 MHz to 18 MHz. In contrast, biodiesel produced from sunflower and different reaction routes led to SoS and Att which were statistically different over the same frequency range, reflecting the ability of ultrasound to monitor low-level contamination of different blends. Finally, the paper concludes that ultrasound shows promise as a means of assessing biodiesel quality and purity with sensitivity sufficient to discern contaminants in a proportion as low as 0.1% in mass for Att measurements.